Survival analysis in rectal carcinoma after neoadjuvant chemoradiation: various methods with different results - Merkel, Susanne; Weber, Klaus; Göhl, Jonas; Agaimy, Abbas; Fietkau, Rainer; Hohenberger, Werner; Grützmann, Robert; Hermanek, Peter (International Journal of Colorectal Disease, 2017)
Survival is an important indicator of outcome quality in rectal carcinoma. The 5-year survival rate is the typical outcome measurement. In patients with neoadjuvant chemoradiation followed by curative surgery, 7 years of follow-up is recommended. Different methods of survival analysis lead to different results. Here, we compared four different methods.The data of 439 patients with rectal carcinoma treated with neoadjuvant chemoradiation followed by curative total mesorectal excision (TME) surgery between 1995 and 2010 were analysed. After stratifying by stage, relative survival (RS), cancer-related survival (CRS), overall survival (OS) and disease-free survival (DFS) were compared. In particular, the 3-year disease-free survival rate was compared to the 5- and 7-year overall survival rates.In the total cohort, the 5-year survival rates ranged from 90% (RS), over 84% (CRS) and 83% (OS) to 72% (DFS). Depending on the stage of disease, the differences between the 5-year survival rates varied between 10 and 32 percentage points. The differences were lowest in UICC stage y0 and highest in UICC stage yIV. The 3-year DFS-rate was always lower (worse) than the 5-year OS rate and higher (better) than the 7-year OS rate, with the exception of stage yIV.Comparisons of survival are only meaningful if the same methods are applied. The 3-year rate of DFS was always worse than the rate of 5-year OS. Therefore, the 3-year rate of DFS appears to be a useful surrogate indicator in rectal carcinoma treatment studies.
EVALuna2:6896